Intellectual Capital Influence on Financial Performance and Company Value - Ardiansari, A; Nugrahaini, M; Wiratno Putri, V (KnE Social Sciences, 2018)
The purpose of this study is to examine the influence of intellectual capital (human capital, structural capital, capital employed) on financial performance and corporate value. The population in this study is a banking company listed on the Indonesia Stock Exchange during the period 2011-2015. The sample is taken by purposive sampling technique that is based on certain criteria. Data analysis in this research use multiple linear regression analysis. The result of hypothesis test shows that human capital and capital employed have positive effect to financial performance, while structural capital does not have positive influence to financial performance. Human capital and capital employed also positively affect the value of the company, while structural capital does not have a positive influence on the value of the company. Thus, companies should pay more attention to the existence of intangible assets that have the potential to improve the financial performance and value of the company. Companies must improve human capital by engaging in budgeting for trainings to improving and developing the employee knowledge. The company must also utilize all its assets so as to maximize the company’s financial performance and value. Keywords: Intellectual Capital, Human Capital, Structural Capital, Capital Employed, Financial Performance, Corporate Value